Keynesianism as a tool how to solve Eurozone Crisis - Havlíček, Tomáš; Žamberský, Pavel; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
In my master thesis I am focusing on the Eurozone crisis and its cures. Based on theory of Keynesianism made by a british economist Keynes I am suggesting several steps that can be taken in order to stop the crisis. My thesis is devided into three main parts. The first one I am criticaly talking about the Keynes's book (The General Theory of Employment, Interest and Money). The second part is about analyzing the crisis of Eurozone. In the last part I am implementing Keynes's theories on the European Union and the Eurozone.
Vedoucí práce: Pavel Žamberský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses